Description of the structure of singular spectrum for Friedrichs model operator near singular point - Serguei I. Iakovlev (International Journal of Mathematics and Mathematical Sciences)
The study of the point spectrum and the singular continuous one is reduced to investigating the structure of the real roots set of an analytic function with positive imaginary part M(λ). We prove a uniqueness theorem for such a class of analytic functions. Combining this theorem with a lemma on smoothness of M(λ) near its real roots permits us to describe the density of the singular spectrum.